Archie E. Roy Dies at 88 - Robertson, Tricia (Journal of Scientific Exploration, 2013)
Archie was Emeritus Professor of Astronomy at the University of Glasgow. An asteroid is named after him in recognition of his contribution to Astronomy: Asteroid 5806 Archieroy. He was a prolific author, and not just on academic topics; in fact, six of his twenty books were novels. Archie's other scientific passion was investigating the paranormal. This interest began when he was a student at the University of Glasgow, when one day while browsing through the University library he came upon books on paranormal topics by noted scientists. His first reaction was "What's all this rubbish doing in a University library?" As he later said to me, at least he had the grace to read some of them. However, he was impressed by much of what he read, and he resolved to pursue the topic further. I met Archie in 1987, and thereafter we embarked on a series of experiments with mediums and healers. Three of our published papers are in the Journal of the Society for Psychical Research, and they document a five-year rigorous practical study of mediumistic information transfer in conditions up to triple blind. Archie was a Fellow of the Royal Astronomical Society and the British Interplanetary Society. He was Past President of the Society for Psychical Research London and the Founding President of the Scottish Society for Psychical Research. Other positions included Patron of the Churches Fellowship, Scotland, for Psychical and Spiritual Studies, and membership in the Scientific and Medical Network. Archie lectured on both of his passions throughout the world. For many years he gave 10-week evening classes in Psychical Research at the University of Glasgow, and seven years ago I collaborated with him to expand this to a 20-week course. Archie was in every sense a gentleman who was liked and respected by everyone, and whose personality and dry sense of humor will be sorely missed. His favorite expression was: If when I die I find that I have not survived, I will be very surprised.